Phytochemical screening and antioxidant activity of wild mushrooms growing in tropical regions - ELISA HERAWATI; RICO RAMADHAN; FARIDA ARIYANI; MARJENAH MARJENAH; IRAWAN WIJAYA KUSUMA; WIWIN SUWINARTI; DJUMALI MARDJI; RUDIANTO AMIRTA; ENOS TANGKE ARUNG (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Herawati E, Ramadhan R, Ariyani F, Marjenah, Kusuma IW, Suwinarti W, Mardji D, Amirta R, Arung ET. 2021. Phytochemical screening and antioxidant activity of wild mushrooms growing in tropical regions. Biodiversitas 22: 4716-4721. This study aims to determine the presence of secondary metabolites which generally have bioactivity that is antioxidant with phytochemical tests and antioxidant tests in Auricularia auricula, Schyzophyllum commune, Microporus xanthopus, and Trametes versicolor fungi that grow in the wild. Phytochemical analysis was carried out by testing color changes and modifications, while antioxidant tests were carried out by using a UV-Vis spectrophotometer and a DPPH solution (1,1-diphenyl-2-picrylhydrazyl). This research found that edible wood fungus that grows, wild such as A. auricula, contains secondary metabolites, namely flavonoids, triterpenoids, saponins, and tannins, but does not contain steroids, alkaloids, carotenoids, or coumarin, while S. commune contains secondary metabolites, namely flavonoids, steroids, tannins, and coumarin, but does not contain triterpenoids, alkaloids, carotenoids, or saponins and non-edible wood fungus, such as M. xanthopus, contains secondary metabolites, namely, flavonoids, saponins, tannins, coumarin, and steroids, but does not contain triterpenoids, alkaloids, or carotenoids, while T. versicolor contains compounds, secondary metabolites, flavonoids, saponin, tannins, coumarin, and triterpenoids, but does not contain steroids, alkaloids, or carotenoids. The antioxidant test results are based on IC50 calculations; it is known that the IC50 value of A. auricula is 499.25 g/mL, while S. commune is 121.37 g/mL, M. xanthopus is 251.20 g/mL, and T. versicolor is 493.04 g/mL. Based on the research results, edible and inedible wood mushroom extracts contain several phytochemicals and show potential for antioxidant activity.